Efektivitas Lama Waktu Perendaman Alat Tangkap Gilnet terhadap Hasil Tangkapan Ikan Layur (Trichiurus sp.) di Pantai Pangandaran - Mutia Dwi Mentari; Achmad Kusyairi (Asosiasi Riset Ilmu Tanaman Dan Hewani Indonesia, 2025)
This researh aims to find out the catch results of Layur fish (Trichiurus sp.) using gilnet fishing tools with different length of soaking time, and to find out the optimum soaking time for improving the effectivenes on cathces of Layur fish. This research was conducted at the Fishery Port Cikidang Pangandaran, West Java in December 2024 with collecting experimental data, interview and processing data. Experimental fishing method is used in this study with different length of soaking time that is 1 hour and 3 hour soaking time. Normality test, homogeneity test and T-test is used for processing data. The trap that was soaked with 3 hours soak time results more at fish accumulation compared to 1 hour soak time with difference 30 fish. Fish accumulation data of Layur fish in tail units at Pangandaran beach shows that the data was normally distributed and homogen based on normality test and homogeneity test. Test result of indepent t-test sample shows using different soak time that is 1 hour and 3 hour makes no difference at quantity catches of Layur fish significally. Field conditions and difference of soak time which is considered too short caused makes no differences significally on fish accumulation.